How Does AI Support Neurodegenerative Disease Research? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2017)
Neurodegenerative diseases, such as Alzheimer's and Parkinson's, are a major health challenge. Artificial Intelligence (AI) is a powerful new tool that is re...
Keywords: AI in Neurology; Support; Neurodegenerative; Disease; Artificial Intelligence; Healthcare; Diagnostics